The Problem of Synthesizing and Harmonizing Science, Religion and Art Based on Artistic-Aesthetic Principles in the Modern Global Spiritual System - Allayarova Marhabo Mavlyanovna (Periodica Journal, 2023)
Globalization processes, together with unprecedented new opportunities for humanity, bring with them unexpected problems - threats and dangers against national identity and spiritual values. In this article, it is analysed how modern scientific and technical development causes dis-harmonization on a global scale - disruption of internal harmony in the spiritual system. One of the main ways to eliminate this danger is the humanization of science, which can be achieved by synthesizing and harmonizing it (science) with religion based on artistic-aesthetic principles.
Keywords: national identity; spiritual values; dis-harmonization